Toxicokinetics of recombinant human fibroblast growth factor 21 for injection in cynomolgus monkey for 3 months - Lu, Chao; Jin, Lei; Bi, Jianing; Jin, Hongyi; You, Xinyi; Peng, Lulu; Fan, Haibing; Wang, Huan; Wang, Liangshun; Fan, Zhengkai; Wang, Xiaojie; Liu, Baohua (Frontiers in Pharmacology, 2023)
Recombinant human fibroblast growth factor 21 (FGF-21) is a potential therapeutic agent for multiple metabolic diseases. However, little is known about the toxicokinetic characteristics of FGF-21. In the present study, we investigated the toxicokinetics of FGF-21 delivered via subcutaneous injection in vivo. Twenty cynomolgus monkeys were injected subcutaneously with different doses of FGF-21 for 86 days. Serum samples were collected at eight different time points (0, 0.5, 1.5, 3, 5, 8, 12, and 24 h) on day 1, 37 and 86 for toxicokinetic analysis. The serum concentrations of FGF-21 were measured using a double sandwich ELISA. Blood samples were collected on day 0, 30, 65 and 87 for blood and blood biochemical tests. Necropsy and pathological analysis were performed on d87 and d116 (after recovery for 29 days). The average AUC(0-24h) values of low-dose FGF-21 on d1, d37, and d86 were 5253, 25268, and 60445 μg·h/L, and the average AUC(0-24h) values of high-dose FGF-21 on d1, d37, and d86 were 19964, 78999, and 1952821 μg·h/L, respectively. Analysis of the blood and blood biochemical indexes showed that PT and AST content in the high-dose FGF-21 group increased. However, no significant changes in other blood and blood biochemical indexes were observed. The anatomical and pathological results showed that continuous subcutaneous injection of FGF-21 for 86 days did not affect organ weight, the organ coefficient, and histopathology in cynomolgus monkeys. Our results have guiding significance for the preclinical research and clinical use of FGF-21.